Factors influencing corporate voluntary disclosures in Malaysia - Ahmed Haji, Abdifatah; Mohd Ghazali, Nazli Anum (Inderscience Enterprises Ltd, 2013)
This study examines factors influencing corporate voluntary disclosures in Malaysian corporate annual reports to see if there has been a change in factors influencing disclosure after the 2007/08 global financial crisis. Multiple regression analyses were run using data from 85 listed companies for the years 2006 and 2009, selected based on systematic stratified random sampling. The quality of disclosure was measured using a self-constructed checklist. A scale of 0 – 3, depending on how an item is disclosed by the company, was used in awarding scores to companies. Results show that company size to be statistically significant in both years. However, profitability and government ownership which were statistically significant at the 5% and 10% levels respectively in 2006 were no longer significant in 2009. The finding on profitability implies that during times of financial crisis, whether a company is operating profitably or otherwise does not have an impact on voluntary disclosure practices. Additionally, board size was marginally significant at the 10% level in explaining the quality of voluntary disclosure in 2009 while board independence remained insignificant in both years suggesting that independent directors are not an effective mechanism for enhancing corporate transparency.